MANAGING WASTE ELIMINATION DATABASE IN LEAN MANUFACTURING: IMPROVE PROBLEM SOLVING CAPABILITY - A. P., Puvanasvaran; Y., Hui Hui; N., Norazlin (Science Publication, 2014)
This study highlighted on managing the waste elimination database in lean manufacturing of the case study company. An application for managing the waste elimination database in lean manufacturing to improve the visual indicators and enhance the problem solving capabilities of the employees in the organization is introduced as the basic success factors to drive the process of continuous improvement culture forward. Ineffective database systems within the organization have caused the inaccurate, redundancy and inconsistency of data. Lean implementations are not successful because there is a lack of communication and involvement of all levels of employees. The study attempts to design an application in a personal database system to the employees at Lean department to keep track of the waste elimination database for analysis and evaluation purpose. Likewise, it’s also examined the employees’ problem solving capacity in waste eliminating project. Application in Microsoft Access is considered new in the case study company. The problems that faced are such as the human factors such as the fearful in changing and accepting IT systems and procedures. Application in Microsoft Access is considered new in the case study company. The employees in Lean department can easily keep track on the improvement projects and the management can monitor on the improvement task and problem solving capabilities of the employees. The visual indicators are improved because meaningful chart and reports are generated for visual and filling purpose. Besides, implementing the problem solving cycle in the designed application to improve the problem solving activities which is also an important element in creating continuous improvement culture. As the many factors such as human factors and skills in using the database application are affected the effectiveness of the designed application. The cost saving value after implementation the database application is difficult to obtain as some study subject are difficult to measure in term of cost.